The Implementation Effect of the Evidence-Based Practice Plan for Rehabilitation Nursing of Stroke Swallowing Disorder - Na, Sa Ri; oyungoo, B.; Bai, Yiping (International Journal of Public Health and Medical Research, 2025)
Objective: To explore the implementation effect of the evidence-based practice plan for rehabilitation and nursing of cerebral stroke and swallowing disorders. Methods: 90 patients with cerebral stroke and dysphagia admitted to a hospital were selected and randomly divided into the experimental group and the control group, with 45 cases in each group. The experimental group implemented personalized nursing based on the evidence-based practice plan, including standardized diet management, swallowing function training and oral care; the control group adopted the traditional nursing model. Evaluate the nursing effect through the drinking water test, SWAL-QOL score and nursing satisfaction, and analyze the changes in the nursing quality of the two groups and the quality of life of patients. Results: The efficiency of nursing quality and swallowing function improvement of the experimental group (97.78%) was significantly higher than that of the control group (80.00%), the quality of life score and nursing satisfaction score are also significantly better than the control group (P